Who pays for renewables? Increasing renewable subsidisation due to increased datacentre demand in Ireland - Muireann Á. Lynch; Mel T. Devine (The Economic and Social Research Institute (ESRI), 2017)
Demand from datacentres makes up a rapidly growing portion of electricity demand in Ireland. Increased demand in turn gives rise to increased renewable generation, mandated by government targets, and a corresponding increase in subsidisation levels. The current method of apportioning renewable subsidy costs may lead to consumers other than datacentres bearing this excess cost of subsidisation. This letter calculates the expected impact on these consumers.
Keywords: Q4; D43; D47; L13; C61; 330; Capacity markets; Reliability; Mixed complementarity problem; Stochastic modelling